Immunostaining with D2–40 improves evaluation of lymphovascular invasion, but may not predict sentinel lymph node status in early breast cancer - Vassallo José (BMC Cancer, 2009)
Abstract Background Sentinel lymph node (SLN) biopsy is a widely used diagnostic procedure in the management of early breast cancer. When SLN is free of metastasis, complete axillary dissection may be skipped for staging in clinically N0 patients, allowing a more conservative procedure. Histological tumor features that could reliably predict SLN status have not yet been established. Since the degree of tumor lymphangiogenesis and vascularization may theoretically be related to the risk of lymph node metastasis, we sought to evaluate the relationship between lymph vessel invasion (LVI), lymphatic microvascular density (LVD), microvascular density (MVD) and VEGF-A expression, with SLN status and other known adverse clinical risk factors. Methods Protein expression of D2–40, CD34, and VEGF-A was assessed by immunohistochemistry on paraffin-embedded sections of primary breast cancer specimens from 92 patients submitted to SLN investigation. The presence of LVI, the highest number of micro vessels stained for D2–40 and CD34, and the protein expression of VEGF-A were compared to SLN status, clinicopathological features and risk groups. Results LVI was detected in higher ratios by immunostaining with D2–40 (p < 0.0001), what would have changed the risk category from low to intermediate in four cases (4.3%). There was no association between LVI and other angiogenic parameters determined by immunohistochemistry with SLN macrometastases, clinical features or risk categories. Conclusion Assessment of LVI in breast carcinoma may be significantly increased by immunostaining with D2–40, but the clinical relevance of altering the risk category using this parameter may not be advocated according to our results, neither can the use of LVI and LVD as predictors of SLN macrometastasis in early breast cancer.